OPTIMALISASI SISTEM KERJASAMA KELOMPOK TANI DALAM MENINGKATKAN PRODUKTIVITAS USAHATANI DI KABUPATEN SUMBAWA - Yakin, Gusmaenul; Asmini, A; Rachman, Rosyidah (Pusat Riset dan Publikasi, 2025)
The farmers' group plays a role as a learning class, a cooperation vehicle, and a production unit. Through the farmers' group, the government can more easily coordinate with farmers, allowing development programs to be effectively communicated and on terget. This study aims to determine the effect of farmer group cooperation system on farming businesses productivity in Sumbawa District. The type of this study was associative study. This study used a quantitative data obtained directly from primary sources, namely 95 farmers in Sumbawa District. Data collection was conducted using a questionnaire as a research instrument. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determinant testing (R2). The results of this study showed that the farmer group cooperation system had a positive and significant effect on farming business productivity in Sumbawa District. The ability of farmer group cooperation system to effect the farming business productivity in Sumbawa District was 15.9%, while the remaining 84.1% was effected by other variables outside this study model, such as land area, labor, production costs, and farming experience.